The Total Synthesis of Spermine Alkaloid Kukoamine Bimesylate - Dong, Kai (Synlett, 2018)
The first total synthesis of kukoamine B bimesylate was completed from 1,4-diaminobutane dihydrochloride in 12 steps with a 11.4% overall yield, and all the steps could be carried out at a kilogram scale. The cyano groups were used as the precursor of amino groups to avoid the competitive reaction delicately. The aza-Michael addition reaction, amidation and hydrogenation of the cyano group sequence was streamlined as a general approach towards the synthesis of polyamine structures.
Keywords: total synthesis; kilogram scale; aza-Michael addition; amidation; hydrogenation